The modern narrator in “The hour of the Star” - Pauka, Gabriela (Revista Letras Raras, 2025)
This paper investigates the modern elements that constitute the narrator of “The Hour of the Star”, the last novel published during Clarice Lispector’s lifetime. Defined by its narrator, Rodrigo S. M., as a “mute photograph,” the book intensely explores the creative process of its fictional author, becoming the analytical focus of this study. The aim is to understand how modern narratives construct a narrator whose voice reveals the impossibility of objective neutrality or absolute omniscience - hallmarks of modern literary production. This analysis contributes to unraveling fundamental questions about modernity and its literature, characterized by the suspension of belief in science, the dissolution of institutions, and the collapse of metanarratives. These dynamics reflect the essence of the modern soul: fragmented, bereft, and self-aware. Examining Rodrigo S. M.'s literary craft allows one to uncover the intricacies of written expression, capturing its “delicate essential.” To map the elements that constitute Rodrigo S. M. as a modern narrator, this article draws on authors such as Theodor W. Adorno, Mikhail Bakhtin, and Anatol Rosenfeld.